The impact of construction quality on the safety of prefabricated multi-family dwellings. (June 2019) - Knyziak, Piotr
Abstract: This study presents analysis of the safety of prefabricated buildings utilizing concrete large-panel technology in the context of building failures as a result of exceptional loads and in the context of their technical condition. Examples of incorrect construction and maintenance from on-site inspections of 110 buildings in Poland are described. Lack of assembly alignment, elements of the structure not protected against corrosion, elements damaged during construction work, no repairs after exceptional loads, and lack of structural strengthening are discussed. The set of case studies of large-panel buildings undergoing partial progressive collapses investigated in this study describe how this type of building, despite the impact of all the imperfections of construction and maintenance, carry exceptional loads. A systematic defining of the degree of advancement of a progressive collapse in residential buildings in relation to typical damage ranges was proposed. Highlights: The ways buildings partially survived a progressive collapse were analyzed. Examples of several failures of large-panel buildings are presented. Results of on-site inspections of 110 large panel buildings were described. Incorrect construction and maintenance of large-panel buildings was identified. Total safety reserves of large-panel buildings are enough to survive emergency situations with limited range.